Yoram Barzel and the Economics of Institutions - Lueck, Dean (Man and the economy, 2019)
This article examines the relationship between the work of Yoram Barzel and Institutional Economics. Barzel has developed a property rights/transaction cost approach to economics and has written on topics ranging from car racing to slavery to Jewish lending to voting rules in condominium associations. Among his many ideas are those about racing to claim assets, multitasking, rationing by waiting, divided ownership of complex assets, measurement costs, and the economic orgins of democracy. In the process Barzel’s work unearthed the economic rationale for many institutions and offered a framework for analyzing them. Barzel holds an important place among all economists for expanding the scope of economic science in a way that focuses attention on the importance of property rights in understanding institutions and the economic logic of their variety. In this way he has been a crucial part of economic study of institutions.